Code-switching among EFL Teachers - Veni Nella Syahputri (English Education Journal, 2018)
This study examined the utilization of code switching used by teachers in English classes. The motivation behind this investigation is to discover the condition that acts as the baseline of code-switching use. This study was merely a qualitative investigation where the data are based on the quality, not quantity. The subjects of this study were 2 English teachers in SMP IT Az-Zahra, Takegon in two English classes in 2015. The data collection process was done by recording the teachers’ speech during teaching using a voice recorder to see in what condition the teachers employed code-switching. The result demonstrates that the recurrence of code switching for topic switch is what happened all the time for 30.4% in the highest rate. While the least used condition to employ code-switching is addressee specification which is only 7% usage from both teachers. Conclusively, the teachers assumed that utilizing code switching to facilitate the educating and learning process can help students grow their understanding, enable them to stick on the point, and help the students certain about conveying meaning.